2006
DOI: 10.1111/j.1365-3016.2006.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of morbidity rates attributable to conditions originating in the perinatal period among newborns discharged from United States hospitals, 1989–90 and 1999–2000

Abstract: Perinatal conditions account for 60% of US neonatal deaths, yet little is known about rates of morbidity attributable to these conditions. To estimate these rates, we analysed newborn hospital discharges from the National Hospital Discharge Survey. We used International Classification of Diseases, 9th Revision, Clinical Modification (ICD-9-CM) codes to classify discharge diagnoses among a weighted, nationally representative sample of newborns discharged from short-stay, non-federal US hospitals. We compared ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 42 publications
2
19
1
Order By: Relevance
“…This study's reported birth trauma rate of 28.6 per 1000 births is higher than many other published rates, but is similar to the rate reported in Tomashek et al. for the years 1999–2000, 8 which is one of the few studies in the literature that provided a recent national estimate of birth trauma. Their national estimates were derived from the National Hospital Discharge Survey and included 55 210 newborns in 1989–90 and 68 678 newborns in 1999–2000 8 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study's reported birth trauma rate of 28.6 per 1000 births is higher than many other published rates, but is similar to the rate reported in Tomashek et al. for the years 1999–2000, 8 which is one of the few studies in the literature that provided a recent national estimate of birth trauma. Their national estimates were derived from the National Hospital Discharge Survey and included 55 210 newborns in 1989–90 and 68 678 newborns in 1999–2000 8 .…”
Section: Discussionsupporting
confidence: 86%
“…In studies conducted primarily at single hospitals, birth trauma has been estimated to occur in 2–7% of all deliveries and is associated with an increased risk of infant morbidity and mortality 3,6,7 . The few studies that provide population‐based national birth trauma estimates report rates ranging from 0.2 to 37 birth traumas per 1000 births 8–10 . The various birth trauma definitions, study populations and methods used throughout the birth trauma literature make comparisons among or meta‐analyses of studies difficult.…”
Section: Introductionmentioning
confidence: 99%
“…[10] It has been reported that of infants diagnosed with HIE, 15 -20% will die in the neonatal period and 25 -30% of survivors will develop permanent neurodevelopmental abnormalities including cerebral palsy. [6] In our study, 62% and 7% of infants with HIE 3 and HIE 2, respectively, died before hospital discharge. Some infants with HIE 2 and most of those with HIE 3 who survive to hospital discharge will have a poor neurological outcome.…”
Section: Discussionmentioning
confidence: 45%
“…Whichever definition is used, the incidence of asphyxia in this study is very high compared with that reported in developed countries (~1 -5/1 000 live births. [5,6] We did not collect data on modifiable factors that may have contributed to this high incidence. A perinatal care survey conducted in South Africa in 2008/9 reported that delay in seeking medical care, inadequate monitoring during labour and lack of facilities were modifiable factors identified in neonates who died from asphyxia.…”
Section: Discussionmentioning
confidence: 99%
“…Here we overview the most systematic studies as published to the issue. One the most reliable issue-related studies performed in the USA has demonstrated the perinatal morbidity comprising 60% of the child death cases giving a general idea of the biggest impact of perinatal complications in childhood [3] and reflecting extensive issue-related problems in corresponding healthcare system as well as massive deficits in knowledge about and/or practical application of targeted prevention and effective treatment of neonatal, perinatal and postnatal pathologies.…”
Section: Global Burden In Newborn Healthcare and The Role Of Perinatamentioning
confidence: 99%